2011
DOI: 10.1098/rsif.2011.0025
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution imaging of the immunological synapse and T-cell receptor microclustering through microfabricated substrates

Abstract: T-cell activation via antigen presentation is associated with the formation of a macromolecular membrane assembly termed the immunological synapse (IS). The genesis of the IS and the onset of juxtacrine signalling is characterized by the formation of cell membrane microclusters and the organization of such into segregated microdomains. A central zone rich in T-cell receptor (TCR) -major histocompatibility complex microclusters termed the central supramolecular activation cluster (cSMAC) forms the bullseye of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…[52] Briefly, MSCs were seeded onto patterned and control PDMS substrata and incubated for 1 hour to allow cells to adhere. Cell media as subsequently removed and cells cultured in CO 2 independent medium (Gibco) supplemented with 10% fetal bovine serum, 1% l-glutamine and 100 IU mg -1 penicillin/streptomycin (Invitrogen).…”
Section: Time-lapse Videomicroscopymentioning
confidence: 99%
“…[52] Briefly, MSCs were seeded onto patterned and control PDMS substrata and incubated for 1 hour to allow cells to adhere. Cell media as subsequently removed and cells cultured in CO 2 independent medium (Gibco) supplemented with 10% fetal bovine serum, 1% l-glutamine and 100 IU mg -1 penicillin/streptomycin (Invitrogen).…”
Section: Time-lapse Videomicroscopymentioning
confidence: 99%
“…Compared to the micropit system developed by Biggs and colleagues (20), the VCP system possesses two distinct advantages. The rate of successful vertical conjugates is significantly higher in our system (~73% vs. 10–15%) due to the novel combination of the micropit system with a single cell trap array, which efficiently guides the cells into the pits.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a micropit system has been developed to achieve high-resolution IS imaging between effector and target cells at low cost (20). However, the loading efficiency of cells in the micropit system alone is low – about 10–15%.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular Composition of Microclusters at the Center of the Synapse-TCR signaling in T cells on planar lipid bilayers takes place in numerous microclusters that take between 70 and 140 nm (14) and vary from 10 to close to a 100 TCR molecules per cluster while in transit to the cSMAC (44). Studies of T cell-APC conjugates immobilized in an upright position on grids showed that larger microclusters measuring about 1.5 m 2 form in these synapses and coalesce in the center by 60 min (45). To study the distribution of microclusters in late-stage synapses in the BT pairs, we applied threedimensional graphical rendering to selected synapses.…”
Section: Distinct Phases Of Molecular Recruitment and Colocalizationmentioning
confidence: 99%